Drug Interaction analysis-Nigella sativa L.seed (Black Cumin) ethanolicextract on antiseizure activity of Phenobarbitone sodium - Joseph, Lovelyn; Puthillath, Rejeesh Edavan; Rao, Sudarshanram Narayan (Asian Journal of Medical Sciences, 2020)
Background: Multidisciplinary therapy is gaining popularity and drug herb interactions is one of the biggest risk factor contributing to therapeutic failures or toxicities. Apart from analysis of one of such Drug-Herb combinations, this work also aims at emphasizing need for ethnopharmacovigilance practices. Aims and Objectives: Herb-Drug Interaction analysis between Nigella sativa seed ethanolic extract and Phenobarbitone sodium in maximal electroshock seizure in Swiss albino mice with a modified isobolographic analysis. Materials and Methods: Experiment model was Maximal electroshock seizure in Swiss albino mice. Dose ratios of the combination tested were NsEE: Phenobarbitone; 3:1(NsEE75%: Pbt25%), 1:1, 1:3. Analysis was done with modified isobolographic analysis. Results: Nigella sativa seed ethanolic extract exhibit synergistic interaction with Phenobarbitone sodium at 1:1 and 1:3 dose ratios and antagonistic interaction at 3:1 combination. The parameter measured was Hind limb tonic extensor phase in maximal electroshock seizure test in Swiss albino mice. Conclusion: The study showed that interaction profile of Nigella sativa extract-phenobarbitone combination is dose dependent and requires well designed posological studies in epileptic patients to formulate dose adjustment guidelines for multidisciplinary therapy with the herb and Phenobarbitone, also to avoid food drug interactions.